Perinatal Anxiety and Depression in Minority Women. Issue 3 (May 2020) - Gennaro, Susan; O'Connor, Caitlin; McKay, Elizabeth Anne; Gibeau, Anne; Aviles, Melanie; Hoying, Jacqueline; Melnyk, Bernadette Mazurek
Abstract : Abstract: Depression and anxiety are common during pregnancy and are experienced at higher rates among women who are racial and ethnic minorities. Because depression and anxiety influence maternal and infant outcomes, intervening to improve perinatal mental health should be a priority for all healthcare providers. However, in the United States, a number of barriers including lack of mental health providers, lack of perinatal behavioral health systems, and stigma, limit access to care. Universal screening has been recommended and here we examine how universal screening can help nurses improve the mental health of childbearing women. Interventions that are currently in use to improve perinatal anxiety and depression are reviewed and include: psychopharmacology, cognitive behavioral therapy, interpersonal psychotherapy, and mindfulness. Recommendations for future research and healthcare system changes are made. Abstract : Approximately 20% of women of racial and ethnic minorities, experience anxiety or depression during pregnancy, potentially leading to negative consequences for mother and child. Barriers to seeking treatment include uncertainty about what is normal, lack of time, difficulty accessing treatment, and stigma. All pregnant women should be screened for depression and referred for treatment. A review of perinatal anxiety and depression, including current treatment options and promising areas of research are presented.